BERKOMUNIKASI SECARA EFEKTIF DALAM TIM - Dewi, Yuni Retna (Universitas Prof. Dr. Moestopo (Beragama), 2013)
When communications tools fungcition at their best, they can go beyond mere facilitation to transformations. Suchwas the case at rosen law firm.based in releigh, north caroline.Lee rosen, the firms owner and chief executive,wanted to replace an expensive, complicate and inflexible computer system that employees relied on for everythingfrom contact list to appointmen calenders to document stroge.the solution he chose for his small law firm was awiki, the same technology that enable nearly 100.000 people around thw world to contribute to Wikipedia.Thewiki certainly helped cut costs and it also did much more. In addition to handling much of the firms documentstorage and formal communication, the wiki introduced an informal social element that is helping employeesbond as a community.many employees have added personal page with information about themselves, helpingemployess get to know their collagues on more intimate level in implementasi the wiki,rosen faced a commonchallenge whit new communications tools,getting people to give up familiar ways of doing things and embracechange.knowing that the value of a company wiki depends on the level of employee contribution and that havingsome of the staff swicht while others cling to old ways would seriously discrupt communication he encouraged usethe new wiki with a friendly competition. For each page an employee created during the three moth competition,he or she was given on possible combination to the company safe,which contained a 1000 cash prize. From timeto time.rosen also forced use of the wiki by publishing important only on the wiki